RECOVERY OF HUMAN DIGINITY; KANTIAN CONSIDERATION - Chinedu Ifeakor; Anselm Ikenna Odo (Universitas Negeri Makassar, 2021)
This paper tends to recover the dignity of human person using Kant’s view point. Human dignity has for long being in a state of pang. It has been in the lowest esteem in the contemporary society; human right abuses, depersonalization of man, and lack of human respect. The researchers adopt expository method in carrying out the work. The researchers conclude that human life is a phenomenon characterized by a high sense of uniqueness. Every human person ought to be properly treated with such uniqueness, bearing in mind that- all are one and the same people.This paper tends to recover the dignity of human person using Kant’s view point. Human dignity has for long being in a state of pang. It has been in the lowest esteem in the contemporary society; human right abuses, depersonalization of man, and lack of human respect. The researchers adopt expository method in carrying out the work. The researchers conclude that human life is a phenomenon characterized by a high sense of uniqueness. Every human person ought to be properly treated with such uniqueness, bearing in mind that- all are one and the same people. Keywords:Recovery, human person and dignity.